Preferential Trade Agreements in the Asia-Pacific Region - Feridhanusetyawan, Tubagus (IMF Working Papers; Working Paper ;, 2005)
Preferential trade agreements (PTAs) in the Asia-Pacific region have proliferated rapidly over the past five years and are creating a complex web of intersecting bilateral and regional trade agreements. This paper describes the proliferation of these PTAs, discusses their characteristics and implementation, and assesses their potential effects. Realizing the potential gains from Asia-Pacific PTAs requires a commitment to liberalize sensitive sectors, to maintain consistent provisions, and to enforce agreements. Other factors, including administrative complications, also could undermine any potential gains.